Evaluation and management of endometriosis. - YOLDEMİR, AHMET TEVFİK (My University, 2023)
The initial diagnostic investigations for endometriosis are physical examination and pelvic ultrasound. The pelvic examination should include a speculum examination and vaginal palpation. Mobility, fixation and/or tenderness of the uterus and site-specific tenderness in the pelvis should be evaluated. Transvaginal ultrasound and pelvic magnetic resonance imaging are recommended to evaluate the extent of the endometriosis and to determine whether any urinary tract or bowel procedures might also be required during surgical resection. Quality of life should be assessed by using the Endometriosis Health Profile-30, its short version EHP-5 or the generic quality of life questionnaire SF- 36. Management of endometriosis is recommended when it has a functional impact (pain, infertility) or causes organ dysfunction. Many gynecological societies have published different guidelines for the evaluation and management of endometriosis. However, the complexity of this disease together with the different available treatments lead to significant discrepancies between the recommendations. Postmenopausal endometriosis should be considered when a patient has a history of symptoms before menopause including dysmenorrhea, dyspareunia, dyschezia, infertility and chronic pelvic pain. Malignant transformation of endometriosis is estimated to occur in about 0.7–1.6% of women affected by endometriosis. Endometriosis is associated with an increased risk of ovarian cancer, specifically clear cell, endometrioid and low-grade serous types.
Keywords: Endometriosis; pelvic pain; infertility; postmenopausal endometriosis; endometriosis recurrence; malignant transformation